Tax Treaty Scrutiny, Proprietary Costs, and Offshore Disclosure in Emerging Markets - Bangkit Dwi Prasetyo; Diana Puspitasari (Inovasi Analisis Data, 2025)
Purpose – We investigate how tax treaty–related governance mechanisms affect firms' disclosure of offshore activities, considering the different incentives they have to avoid taxes. Design/methodology/approach – We examine structural relationships using a theory-based survey design and partial least squares structural equation modelling. Findings – Individuals who are knowledgeable about tax treaties are more likely to disclose offshore information. However, they are less likely to do so if they believe that this will result in information exchange, higher costs, or stricter scrutiny by tax authorities. There is also reason to believe that people are motivated to avoid sharing information, which may exacerbate the negative impact of the perception of information sharing on offshore information disclosure. This suggests that people make strategic decisions about transparency in the face of higher enforcement risk. However, the moderating impact of tax avoidance motives varies depending on the type of enforcement pressure, suggesting that firms at opposite ends of the spectrum respond differently to disclosure. Originality/value – This study integrates disclosure, tax avoidance, and enforcement theories, revealing how managerial treaty perceptions shape offshore disclosure incentives. Research Implications – The results suggest that working together on taxes might accidentally stop people from sharing information, especially when companies want to avoid taxes. This means we need to pay more attention to making sure people follow the rules, being open about what we're doing, and how managers behave, if we want to have a better global system.